Management of obstetric hemorrhage; an observational study highlighting the efficacy of uterine artery ligation - Ghouri, Ambreen; Mushtaq, Bushra; Ahmed, Azra; Dalwani, Najma; Bai, Padma; Tariq, Anas Bin (International Journal of Research in Medical Sciences, 2020)
Background: Obstetrical hemorrhage is leading cause of maternal mortality. UAE is termed safe and effective method for resolving hemorrhage. objective of this study was to determine efficacy of uterine artery ligation in management of obstetrical hemorrhage. Methods: This cross sectional observational using non-probability convenient sampling technique was carried out for six months. After ethical approval, females between 18 to 35 years diagnosed with obstetrical hemorrhage, uterine atony refractory to medical treatment, having active bleeding from placental side or having normal coagulation profile were while females with post-partum hemorrhage because of retained products of conception, due to genital tract trauma or with disseminated intravascular coagulation were excluded. Analysis of data was done using SPSS version 23.0. Quantitative variables were reported as mean and standard deviation and for qualitative variables, frequency and percentages. Chi-square test was applied keeping p-value of <0.05 as statistically significant. Results: From 109 females with mean age 47±5.25 years. In comparison of parity distribution, 62 (56.88%) were multiparous and 47 (43.12%) were primiparous. Type of bleeding observed was antepartum 36(33.03%), peripartum 39 (35.78%) and postpartum in 34 (31.19%). Efficacy of uterine artery ligation in management of obstetric hemorrhage was observed to be 35 (32.11%). The efficacy of uterine artery ligation in management of obstetric hemorrhage in three categories of age groups reported significant association (p=0.0005) and type of bleeding (p=0.025). Conclusions: Efficacy of UAE in different types of obstetrical hemorrhage reported in our study was lower than expected in about one-third of females.